PENINGKATAN PENGETAHUAN ANIMASI VIDEO DAN ROBOTIK DALAM PENERAPAN PROJECT BASE LEARNING DI SMA IT BAITUL JANNAH - Arlina Phelia; Galuh Pramita; Try Susanto; Agus Widodo; Rio Aditomo Mahardika Putra (JURNAL CEMERLANG : Pengabdian pada Masyarakat, 2021)
Improving the quality of education makes technological developments increase as well and forces various parties to be able to participate in all forms of activity. Facing these challenges, teachers are required to better master information technology and the direct application of science and technology in schools. One of the concepts that can be developed for schools is the PjBL concept based on information systems and computers. One of the things that teachers need is learning in making video animations, while in adding new insights students need to improve skills in conducting practicals in schools such as knowledge about robotics. After socializing the teachers and students of SMA IT Baitul Jannah, the evaluation results from counseling related to the introduction of simple robotics were 90.44% of students who did not know simple robotics to 100%. For the evaluation of counseling related to learning using video animation applications, it was found that 97.62% stated that they did not know clearly the applications that could be used in making video animations to 100%. This is an increase in students and teachers who want to improve understanding of simple applications and can easily develop animated learning media and develop simple robotic practices.